Pharmacology and mechanisms of apigenin in preventing osteoporosis - Lin, Sun; Yincang, Wang; Jiazhe, Du; Xilin, Xu; Zhang, Xiaofeng (Frontiers in Pharmacology, 2024)
Osteoporosis (OP) stands as the most prevalent systemic skeletal condition associated with aging. The current clinical management of OP predominantly depends on anti-resorptive and anabolic agents. Nevertheless, prolonged use of some of these medications has been observed to reduce efficacy and elevate adverse effects. Given the necessity for sustained or even lifelong treatment of OP, the identification of drugs that are not only effective but also safe and cost-efficient is of utmost significance. As disease treatment paradigms continue to evolve and recent advancements in OP research come to light, certain plant-derived compounds have emerged, presenting notable benefits in the management of OP. This review primarily explores the pharmacological properties of apigenin and elucidates its therapeutic mechanisms in the context of OP. The insights provided herein aspire to offer a foundation for the judicious use of apigenin in forthcoming research, particularly within the scope of OP.